The Implementation of SQ3R Method for Teaching English Reading Text - Tiffani Ramadhani Pribadi; Sujatmiko Sujatmiko (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
Problems that arise during online learning must be addressed immediately, including learning to read English. Many students do not achieve effective learning and tend to rely on smartphones instead of using the results of their own ideas and thoughts. The SQ3R method is a method for learning reading that can help students understand English texts with the analysis stage and generate ideas and creativity from their own minds. This study aims to determine: How to implementation SQ3R method in online English learning. This research is a qualitative research by describing how the implementation of the SQ3R method and the results of the SQ3R method that have been carried out online. The participants in this study were 25 students of grade 8F at SMP N 1 Tempel . Collecting data in the form of student interview questionnaires, transcripts of teacher interviews and photos of the implementation of the SQ3R method online. Through research instruments in the form of interviews, questionnaires and documentation. The collected data were analyzed descriptively in the form of presentation tables and presentation of interview transcripts and questionnaires. The first stage of data collection in this study was teacher and student interviews, then applied the SQ3R method to students and documentation of the results of the SQ3R method applied by students. The results of implementation of SQ3R method indicate that the SQ3R method can be applied online by enabling teachers to create media that can help students understand the SQ3R method.